More money for Europe: Agreement on a new EU financial framework for 2007-2013 - Peter Becker (Stiftung Wissenschaft und Politik (SWP), 2006)
By reaching a political consensus on a new Financial Framework in mid-December 2005, at best the European Union can be said to have finally struck a deal and demonstrated its ability to act. However, the compromise reached by the European heads of state and government by no means marks the end of the marathon negotiations that began way back in February 2004. Indeed, first the Council of Ministers must haggle with the European Parliament over the new Financial Framework; then the 25 EU Member States' respective national parliaments will have to ratify a new Own Resources Decision. Moreover, the fact that the European Parliament so flatly rejected the compromise reached at the Brussels Summit is a clear indication of just how difficult this final phase of the process will turn out to be. (SWP Comments / SWP)
Keywords: 320